Uncertified and Teaching: Industry Professionals in Career and Technical Education Classrooms - Geralyn E. Stephens (European Research Network Vocational Education and Training (VETNET), 2015)
Industry professionals are permitted to teach in Michigan's federally funded Career and Technical Education (CTE) secondary programs, before completing a teacher certification program, under the Annual Occupational Authorization (AOA) provision. This study reviews their academic foundations, professional credentials and their pedagogical knowledge and skill levels. Findings include that most AOA teachers possess post-secondary academic credentials and extensive service records in their previous industry careers. The study identified relationships between the age and educational backgrounds of AOA teachers and their use of specific instructional activities and a statistical relationship between their years teaching in the CTE classroom and the degree of collaboration with academic, industry and occupational colleagues. While AOA teachers are confident in their ability to share occupational knowledge and skills, they lack an extensive awareness of authentic assessment strategies. Recommendations include establishing Teacher Mentoring programs, where both academic and occupational peers serve as mentors to AOA teachers